Is academic spin-off financing a matter of business and growth models? The Spanish case - Martínez-Martínez, Sofía Louise; Cisneros-Ruiz, Ana José; Ventura-Fernández, Rafael; Cisneros-Ruiz, Ana José; Diéguez-Soto, Julio (Emerald)
Purpose. This study investigates the relationship between the development of academic spinoffs (ASOs) and the type of financing involved, by considering three research questions: How do ASOs differ in terms of financing? To what extent and for what reasons do ASOs differ in their financing? How do business and growth models dictate the selection of different sorts of financing arrangement? Design/Methodology/approach. The study employs a grounded-theory, qualitative approach based on 39 Spanish ASOs. Findings. There is a heterogeneity of ASO financing, and the selection of financial resources is related to the business and growth model of the ASO. Furthermore, there are some critical junctures for financing within each group of ASOs. Research limitations/implications. The study advances the understanding of the determinants of ASOs, specifically with respect to financing, business models, and growth orientation. The Spanish context used here may not permit the global generalisation of the results; nevertheless, this study is a response to calls to consider the effect of regional context on ASOs. Practical implications. Knowing the heterogeneity of ASOs in terms of financing and how business and growth models determines the selection of distinct financing sources help financial planning, investment decisions and the design of programs and policies, which can be relevant for both ASOs and their stakeholders (investors, universities, and governments). Originality/value. This study provides a comprehensive view of ASO financing, confirming a heterogeneity, not only in terms of financing but also in some critical junctures that presage a change from one type of financing to another.
https://openpolicyfinder.jisc.ac.uk/id/publication/2724
Keywords: Spin-off académicos; Transferencia de tecnología; Academic entrepreneurship; Entrepreneurial university; Spin off; Technology transfer